Transcriptome profiling reveals the role of XIST/miR-335-5p regulatory axis as a crucial mediator of chemoresistance in esophageal cancer by influencing EMT and Ferroptosis - Kiran Pasbola; Anoop Saraya; N. R. Dash; Deepak Gunjan; Kailash Kurdia; Geetika Suyal; Rinu Sharma (Functional & Integrative Genomics, 2026)

An explainable deep learning-integrated decision support system for field diagnosis and management of botrytis grey mold in castor - G. Jadesha; Yamanura Madival; R. Mohan Kumar; Anurag Dhole; H.C. Lohithaswa; Mallana Gowda Mallikarjuna; K.B. Palanna; D. Deepak (Computers and Electronics in Agriculture, 2026)

Development of biomimetic mouldable osseous scaffold engineered from bioactive decellularized extracellular matrix-polymer-gel composite: a potential bone substitute - Prarthana R; Rekha Pathak; Deepak Kumar; Vinodhkumar Obli Rajendran; KS Kamalesh; T. Saikumar; Bhanu Pratap Singh; Rohit Kumar (Cell and Tissue Banking, 2026)

Functional morphotypes as proxies for large-scale assessment of marine nematode assemblages along the Indian coastline - Sanofar Khokher; Joydeep Dutta; Elisa Baldrighi; Amita Choudhury; Abhilash K. R.; Deepak Samuel (Regional Studies in Marine Science, 2026)

Numerical and experimental investigation of a Coandă-effect-based hydraulic collector for deep-sea polymetallic nodules - Amudha K.; Deepak Kumar; Gopkumar K.; Balaji R.; Rajiv Sharma (Ocean Engineering, 2026)

Electrifying Sagar Island, West Bengal, India: advancing multiple SDGs through integrated coastal policy and sustainable development - Satyendra Kumar; Selvin Pitchaikani J; Deepak Samuel V; Ramesh R (Journal of Coastal Conservation, 2026)

Preclinical investigation of hydroxychloroquine loaded ethosomal gel for topical treatment of rheumatoid arthritis - Pradip Nirbhavane; Deepak Mourya; Ankit Raj; Shivam K. Chaudhari; Kalpesh R. Patil; Shailesh Chalikwar; Kailas K. Moravkar (Inflammopharmacology, 2026)

Evaluating diffusion in swelling clay-amended barriers using modified double reservoir diffusion chamber experiments - Ekta Chaudhary; Deepak Swami; Nitin Joshi; Krishna R. Reddy (Applied Clay Science, 2026)

Unsupervised machine learning techniques for the analysis of mass spectra from CHACE-2 aboard Chandrayaan-2 orbiter - A.K. Ushas; M.B. Dhanya; S. Deepak; H. Viji; Jerrin Thomas Panachakel; Smitha V. Thampi; R. Satheesh Thampi (Advances in Space Research, 2026)

Scaling the Spatial and Temporal Effects of Wrack Disturbance Across a Saltmarsh Landscape - Matt J. Pierce; Tyler Lynn; Julie Grissett; Shelby Ziegler; Sydney Williams; Satyatejas Reddy; Samuel Dong; Cailyn Bowser; Merryl Alber; Steven C. Pennings; Deepak R. Mishra; Amanda C. Spivak; et al. (Estuaries and Coasts, 2026)
Disturbance effects are rarely distributed uniformly over space or time. Thus, scaling up the effects of disturbances requires detailed measurements across multiple spatial scales. To characterize disturbance from wrack we used monthly images from an unmanned aerial vehicle (UAV) in a 144,500 m 2 Spartina alterniflora saltmarsh on Sapelo Island, Georgia (USA), from March 2020 to December 2022. Prior work as well as the results of our study demonstrated that wrack persisting for ≥ 2 months (“persistent wrack”) affects underlying vegetation. During our study, persistent wrack comprised ~ 30% of the average monthly wrack area (161 m 2 or ~ 0.10% of the total S. alterniflora marsh) and showed an annual peak between July and September. We quantified the effects of persistent wrack on live S. alterniflora , two invertebrate taxa (snails and burrowing marsh crabs), and porewater via field surveys of paired wrack-affected and wrack-free controls. At each monthly sampling point relative to controls, S. alterniflora stem density in wrack-affected plots was 41% lower on average and snail density lower by 25%, while crab burrow abundance and porewater parameters remained similar between controls and disturbed plots. Using wrack area from monthly UAV imaging, we scaled-up plot-level effects to marsh-level and found a < 1% change per species in abundance. Thus, our data suggest that even if wrack has strong local effects, the effects can be minor in S. alterniflora marshes at a landscape scale. This study demonstrates that field monitoring to quantify the effects of disturbances, coupled with repeat UAV imagery, allows for scaling that better contextualizes the overall impact than either method alone.

Development of multivariate health index for tropical seagrass meadows: a case study from Pulicat Lagoon, India - C. Viswanathan; J. Joyson Joe Jeevamani; K. Balachandar; K. Arumugam; K. Paramasivam; Dipnarayan Ganguly; R. Muruganandam; V. Deepak Samuel; R. Purvaja (Environmental Monitoring and Assessment, 2026)

Dialogue, inclusion, and adaptation in a remote marine sanctuary: evidence from Flower Garden Banks - Kelly H. Dunning; Daniel Morris; Nadia Bowles; Caleb Camus; Frederic Castruccio; Deepak Cherian; Denise Cole; Jaliyl Collins; Tommy Furland; Joanie Kleypas; Kristen Krumhardt; Gretchen Luchauer; et al. (Environmental Management, 2026)
Interdisciplinary, stakeholder-engaged research is increasingly being used for managing climate change in social-ecological systems. We apply a Collaborative Adaptive Experimental Governance lens to the Flower Garden Banks National Marine Sanctuary, a remote, relatively pristine coral reef system ~130–190 km offshore in the Gulf of Mexico, where biodiversity protection coexists with recreation and offshore energy. We coupled participatory social science with climate and ecosystem modeling to inform dialogue with decision-makers and users. First, we generated scenarios using Community Earth System Model2-LE ocean temperature and aragonite saturation state to characterize warming and acidification; translated heat stress into a variability-based coral bleaching index; and projected demersal and pelagic fish biomass. We then conducted 37 semi-structured interviews (managers, oil and gas, commercial and recreational fisheries, dive operators, Non-governmental organizations, and science/education), employed multi-coder reliability, and triangulated findings with policy and legal documents. Results highlight the centrality of the Sanctuary Advisory Council in structuring inclusive dialogue, co-producing recommendations, and supporting outreach in distant coastal communities. Multi-level coordination among NOAA, the Gulf of Mexico Fishery Management Council, and the Bureau of Ocean Energy Management enabled boundary expansion and reconciled conservation with industry and fishing interests. Key barriers to adaptive responses include offshore remoteness and logistics, limited public awareness, funding constraints, trust deficits, and procedural delays; pressures that intersect with warming, acidification, and episodic hypoxia. Our study shows that remote marine protected areas can operationalize inclusive, experimental governance to align science and management, but sustained investment in monitoring, restoration capacity, boundary-spanning outreach, and cross-agency coordination is needed.

Fruit Cracking in Litchi Under Changing Climatic Conditions: Causes, Mechanisms, and Mitigation Strategies - Amrutrao H. Patil; Balasaheb Purane; Govind Shiurkar; Deepak Singh; N. R. Rangare; Vijay Bagare; Priyanka Dubey (Applied Fruit Science, 2026)

Integrating omics and artificial intelligence with plant tissue culture: pathways to next-generation crop improvement - Himanshu Saini; Jyoti Yadav; Anand Kumar; Sharad Sachan; Shalu Vyas; Atin Kumar; Deepak Nanda; P. R. Jeyaramraja (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Unraveling cellular longevity pathways in poultry under heat stress: functional and computational characterization of the adaptogenic formulation Phytocee™ - K. Shamana; R. Edwin; S. P. Jaishree; D. Prashanth; G. Aboli; M. Deepak (In Silico Pharmacology, 2026)

Inclusion of social values, priorities, and motivations for mangrove conservation in Bhitarkanika, India - Dina Nethisa Rasquinha; Nibedita Mukherjee; Deepak R. Mishra (Journal for Nature Conservation, 2026)

Cadmium toxicity in the black clam Villorita cyprinoides (Gray 1825): insights for developing seawater quality criteria - K V Neethu; N Deepak Sankar; P Hari Praved; S R Marigoudar; K V Sharma (Journal of Earth System Science, 2026)

Antioxidant, antibacterial and antibiofilm activities of Pittosporum napaulense (DC.) against drug-resistant Staphylococcus aureus and Shigella sp - Sajna Sameekshya Hota; Dibya Ranjan Sahoo; Subhaswaraj Pattnaik; Monika Mishra; Tapasa Mishra; Tanuja Sahu; Baishali Basundhara Naik; Malayamarutham Kalyankumarraju; Amit Kumar Dixit; Deepak Lamba; Sanjaya Kumar Y. R.; Rabinarayan Acharya; et al. (Natural Product Research, 2026)

Facial onset sensory and motor neuronopathy: a diagnostic challenge - Chinmayi Seemikeri; Deepak Menon; Saraswati Nashi; Faheem Arshad; P. R. Srijithesh; Suvarna Alladi (Acta Neurologica Belgica, 2026)

Therapeutic potential of Bergenia ciliata against lung cancer: an integrative molecular docking, ADMET, and molecular dynamics approach - Krittika Mukherjee; Sounok Sengupta; Ajay Kumar Singh; Rajiv Tonk; Shavkatjon Azizov; R. P. Rajwade; Deepak Kumar (In Silico Pharmacology, 2026)

Challenging the Alternaria, great havoc of concern to many crop plants with special reference to sunflower- epidemiology and integrated management - Ajith C R; Sudheendra A. Ashtaputre; Laxminarayana Rao M. S.; Vijayakumar A. Giritammannavar; Milind P. Potdar; Ramaraddi N. Madalli; Deepika Gakhar; Deepak Bhanot; Anurag Malik (Journal of Plant Pathology, 2026)

Two decades of flood-pulse-driven chlorophyll-a dynamics in an Amazon floodplain lake - Ana Clara de Lara Maia; Anna Beatriz Silva Alves; Hulair Braga Carneiro; Lucas de Oliveira Arice; Nathalia Moraes Desani; Raiane Helena da Silva Santos; José Roberto Mantovani; Yasmim Carvalho Guimarães; Thanan Rodrigues; Deepak R. Mishra; Edward Park; Enner Alcântara (Science of The Total Environment, 2026)

Variability of landslide susceptibility models under different ground motion scenarios in Rasuwa district, Nepal - Manoj Thapa; Ananta Man Singh Pradhan; Deepak Chamlagain; Junle Jiang; Netra R. Regmi (Natural Hazards, 2026)

Biochar as a sustainable alternative to conventional carbon additives in iron ore pelletization - Deepak Nayak; Subhashree Nayak; Ammasi Ayyandurai; R. Sathish; Nilima Dash; Swagat S. Rath (Fuel, 2025)

Continuous flow high-pressure homogenization enhances nutrient retention, antioxidant activity, and probiotic growth potential in grapefruit juice during cold storage - Jayashan Adhikari; Lida R. Araghi; Deepak K. Jha; Rakesh K. Singh; Koushik Adhikari; Bhimanagouda S. Patil (Food Research International, 2025)

Genome Wide Identification, Expression Profiles and Regulatory Network Analysis of SOS Group of Genes in Camellia Sinensis - Surjit Bhattacharjee; Abhirup Paul; Aradhana Jana; Deepak R; G. Meher Unnati; Wang Li; Archita Chatterjee; Chen Lin; Guoxin Shen; Neelam Mishra (Tropical Plant Biology, 2025)

Molecular regulation by ubiquitin-specific proteases (USPs) in HCC: cell cycle, oncogenic signaling, and beyond - Furqan N. Al-Khateeb; Asraa Yacoob Yousif; Sarmad Ghazi Al-Shawi; Ali G. Alkhathami; Roopashree R.; Aditya Kashyap; Deepak Nathiya; Subhashree Ray; Mohammed Jawad Alnajar; Muthana Kareem (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Advancements in CRISPR/Cas technology for generating herbicide tolerant crops: a comprehensive review - Dasari Sreekanth; Deepak Vishwanath Pawar; I. K. Sahadeo; Rajeev Kumar; P. S. Basavaraj; Survi Mahesh; C. R. Chethan; Satendra K. Mangrauthia; Shobha Sondhia; P. K. Singh; J. S. Mishra (Journal of Plant Biochemistry and Biotechnology, 2025)

Influence of modified atmospheric storage conditions on seed longevity and health of maize genotypes (Zea mays L.) - T. N. Deepak; S. N. Vasudevan; Palanimuttu; P. Mahadevu; M. Shobharani; R. Siddaraju; Parashivamurthy; Thimmegowda (Cereal Research Communications, 2025)

A remote sensing algorithmic framework for characterizing chromophoric dissolved organic matter in lagoon-estuarine systems - Ishan D. Joshi; Abhishek Kumar; Sambit Singh; Susmita Raulo; Tamoghna Acharyya; Deepak R. Mishra (Science of The Total Environment, 2025)

Monsoon driven interplay between phytoplankton size classes and trophic status in a tropical coastal lagoon - Sambit Singh; Susmita Raulo; Tamoghna Acharyya; Anu Gopinath; Pradipta R. Muduli; Deepak R. Mishra; Gurdeep Rastogi (Science of The Total Environment, 2025)

Toward accurate estimation of respiratory rate from the photoplethysmogram: effect of different window period of PPG signals - M. S. Ganeshmurthy; R. Periyasamy; Deepak Joshi (Physical and Engineering Sciences in Medicine, 2025)

Effect of Phalaris minor and Medicago denticulata on Wheat Growth and Yield Under Drought Stress: Physiological and Biochemical Insights - Dasari Sreekanth; Deepak Vishwanath Pawar; P. S. Basavaraj; Rajeev Kumar; Survi Mahesh; C. R. Chethan; A. Jamaludheen; Shobha Sondhia; P. K. Singh; J. S. Mishra (Journal of Plant Growth Regulation, 2025)

Spatial modelling of soil erosion in sub-tropical region of Central India using AHP and geospatial approach - Ashwini Suryawanshi; Gangalakunta P. Obi Reddy; Nirmal Kumar; Benukantha Das; Deepak Mohekar; Roshan R. Wakode; Burhan U. Choudhury; Meesala Siva Shankar Nagaraju (Environmental Monitoring and Assessment, 2025)

Trends and advances in liposome formulation technology with an emphasis on ensuring safety and quality in food and drug applications - Pawan Prabhakar; Soubhagya Tripathy; Deepak Kumar Verma; Smita Singh; Mamta Thakur; Amit Kumar Singh; Prem Prakash Srivastav; Mamoni Banerjee; Ami R. Patel; Mónica L. Chávez González; Gemilang Lara Utama; José Sandoval-Cortés; et al. (Food Bioscience, 2025)

Elucidating the interactive effects of drought, weeds, and herbicides on the physiological, biochemical, and yield characteristics of rice - Dasari Sreekanth; Deepak Vishwanath Pawar; Survi Mahesh; C. R. Chethan; Shobha Sondhia; P. K. Singh; J. S. Mishra; Nagaraju Mukkamula; B. Kiran Kumar; P. S. Basavaraj (Plant and Soil, 2025)

Top-down control: microzooplankton grazing impact on phytoplankton biomass and community composition in a tropical monsoon driven lagoon, Chilika, India - Sambit Singh; Susmita Raulo; Tamoghna Acharyya; Anu Gopinath; Pradipta R. Muduli; Deepak R. Mishra; Gurdeep Rastogi (Aquatic Ecology, 2025)

Prediction of lightning events over Bangladesh: A machine learning perspective - Kumarjit Saha; Deepak S. Bisht; R. Ashrit (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Managing the recovering saltwater crocodile population in a marine protected area with human-wildlife conflict: A population viability analysis approach - V. Deepak Samuel; J. Joyson Joe Jeevamani; Yusuke Fukuda; R. Muruganandam; Meeta Biswal; R. Ramesh; R. Purvaja (Journal for Nature Conservation, 2025)

Functional Diversity of Seagrass-associated Macrofaunal Assemblages in a Brackishwater Lagoon of India: A multi-trait Approach - K. Paramasivam; K.R. Abhilash; C. Praveen Raj; C. Viswanathan; R. Sankar; J. Joyson Joe Jeevamani; Darwin Ramteke; V. Deepak Samuel; R. Purvaja (Thalassas: An International Journal of Marine Sciences, 2025)

Assessment of polymetallic nodules in the Central Indian Ocean Basin: factors influencing distribution patterns through high‑resolution autonomous underwater vehicle (AUV) survey - V. B. Subin Raj; M. A. Sarun Lal; R. S. Gowri; S. Ramesh; N. R. Ramesh; R. Ramesh; V. Deepak; A. Vadivelan; G. A. Ramadass (Geo-Marine Letters, 2025)

BRCAIndica: a resource for ACMG/AMP classified BRCA1 and BRCA2 variants - Aastha Vatsyayan; R. I. Anu; Prerika Mathur; Divya Uchil; Ashish Joshi; Aradhana Dwivedi; Bhawna Sirohi; Aju Mathew; Dileep Damodaran; Soumya Surath Panda; Spoorthy Kolluri; Shaji K. Ayillath; et al. (Familial Cancer, 2025)

Expanding the flooding in Landsat across tidal systems model to Landsat 5–9 imagery for long-term marsh inundation analysis - Asa R. Julien; Caroline R. Narron; Deepak R. Mishra (Science of The Total Environment, 2025)

Mercury speciation in a complex tropical estuarine system: Understanding natural and anthropogenic influences - Prasad P. Padalkar; Parthasarathi Chakraborty; Soham Chatterjee; Debashish Pradhan; Deepak R. P; Arindam Sarkar; Saranya Jayachandran (Regional Studies in Marine Science, 2025)

Phytophagous probiotic foods: Exploring the intersection of characteristics, quality implications, health benefits, and market dynamics - Alaa Kareem Niamah; Shayma Thyab Gddoa Al-Sahlany; Hussein Katai Abdul-Sada; Pawan Prabhakar; Soubhagya Tripathy; Basant Kumar Dadrwal; Smita Singh; Deepak Kumar Verma; Alok Kumar Gupta; Rakesh Mohan Shukla; Mamta Thakur; Ami R. Patel; et al. (Trends in Food Science & Technology, 2024)

Tasar Silkworm Pupae oil: A potential therapeutic and edible lipid source to mitigate the oxidative stress and cholesterol complications associated with diabetes - Devika Srivastava; Prashant Pandey; Deepak Kumar Tripathi; Jagat Pal Yadav; Bulbul Ali; Vandana Singh; Abhishek Verma; Akash Mishra; Dinesh Kumar; Abha Mishra; Paruvathanahalli Siddalingam Rajinikanth; Krishna Mohan Poluri; et al. (Food and Humanity, 2024)

Climate Impact Prediction: Whale-Optimized Conv-XGBoost with Remote Sensing and Sociological Data - R. Jayakarthik; Chandrashekhara K.T; O. Sampath; Deepak Kumar; Laxmi Biban; Jnaneshwar Pai Maroor; S. N. Lakshmi Malluvalasa (Remote Sensing in Earth Systems Sciences, 2024)

Sensitive electrochemical detection of methimazole based on a unique copper and exfoliated graphene oxide nanocomposite - Lanting Qian; Deepak Sridhar; Tony Shi; Joshua van der Zalm; Antony R. Thiruppathi; Mario C. Guerreiro; Aicheng Chen (Chemosphere, 2024)

Multi-location evaluation of field pea in Indian climates: eco-phenological dynamics, crop-environment relationships, and identification of mega-environments - Ashok K. Parihar; Kali Krishna Hazra; Amrit Lamichaney; Debjyoti Sen Gupta; Jitendra Kumar; R. K. Mishra; Anil K. Singh; Anuradha Bhartiya; Parvaze Ahmad Sofi; Ajaz A. Lone; Sankar P. Das; Rajesh Kumar Yadav; et al. (International Journal of Biometeorology, 2024)

Unraveling molecular architecture, development and validation of Anthocyanin1 gene-based novel breeder-friendly markers for utilization in genomics-assisted breeding of blue maize - Gaurav Sharma; Rashmi Chhabra; Vignesh Muthusamy; Rajkumar U. Zunjare; Govinda Rai Sarma; Deepak R. Sapkal; Firoz Hossain (South African Journal of Botany, 2024)

Dynamics and source characterization of chromophoric dissolved organic matter (CDOM) in a tropical monsoon driven lagoon - Sambit Singh; Susmita Raulo; Tamoghna Acharyya; Deepak R. Mishra; Abhishek Kumar; Anu Gopinath; Pradipta R. Muduli; Gurdeep Rastogi (Marine Chemistry, 2024)

Numerical Modeling of Flow in the Cerebral Vasculature: Understanding Changes in Collateral Flow Directions in the Circle of Willis for a Cohort of Vasospasm Patients Through Image-Based Computational Fluid Dynamics - Angela Straccia; Michael C. Barbour; Fanette Chassagne; David Bass; Guilherme Barros; Daniel Leotta; Florence Sheehan; Deepak Sharma; Michael R. Levitt; Alberto Aliseda (Annals of Biomedical Engineering, 2024)

Environmental drivers behind the exceptional increase in cyanobacterial blooms in Okavango Delta, Botswana - Jan Veerman; Deepak R. Mishra; Abhishek Kumar; Malvern Karidozo (Harmful Algae, 2024)

Angiotensin-I-converting enzyme and renin inhibitions by antioxidant shrimp shell protein hydrolysate and ultrafiltration peptide fractions - Avtar Singh; Deepak Kadam; Akanksha R. Gautam; Kannan R.R. Rengasamy; Rotimi E. Aluko; Soottawat Benjakul (Food Bioscience, 2024)

Flow and contaminant transport dynamics in clay-amended barriers through flushing experiments and multi-porosity-based modeling - Ekta Chaudhary; Deepak Swami; Nitin Joshi; Krishna R. Reddy (Environmental Pollution, 2024)

Correction: On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Assessment of beach morphological characteristics and conservation strategies for blue flag beaches on the West Coast of India - J. Selvin Pitchaikani; Subbareddy Bonthu; R. Muruganandam; C. Viswanathan; K. K. Manodheepan; V. Deepak Samuel; Purvaja Ramachandran; R. Ramesh (Journal of Coastal Conservation, 2024)

Miniaturizing Power: Harnessing Micro-Supercapacitors for advanced micro-electronics - Qazi Muhammad Saqib; Abdul Mannan; Muhammad Noman; Mahesh Y. Chougale; Chandrashekhar S. Patil; Youngbin Ko; Jungmin Kim; Swapnil R. Patil; Muhammad Yousuf; Rayyan Ali Shaukat; Young Pyo Jeon; Deepak Dubal; et al. (Chemical Engineering Journal, 2024)

Impact of the Different Chemical-Based Decellularization Protocols on the Properties of the Caprine Pericardium - Thirumalai Deepak; Deepak Bajhaiya; Anju R. Babu (Cardiovascular Engineering and Technology, 2024)

Potable water production through a low-cost single chamber solar still in north India - Vinay Mishra; Dhananjay Singh; Ram Sharan Singh; Deepak Singh; Eldon R. Rene; Balendu Shekher Giri; Sarthik Sharma; Anurag Mishra; Harishchandra Shukla (Environmental Science and Pollution Research, 2024)

Polyethylene terephthalate waste derived nanomaterials (WDNMs) and its utilization in electrochemical devices - J. Manjunathan; K. Pavithra; Senthilkumar Nangan; S. Prakash; Kuldeep K. Saxena; Kuldeep Sharma; Khursheed Muzammil; Deepak Verma; Jenita Rani Gnanapragasam; R. Ramasubburayan; M. Revathi (Chemosphere, 2024)

The role of living labs in cultivating inclusive and responsible innovation in precision agriculture - Maaz Gardezi; Halimeh Abuayyash; Paul R. Adler; Juan P. Alvez; Rubaina Anjum; Appala Raju Badireddy; Skye Brugler; Pablo Carcamo; David Clay; Ali Dadkhah; Mary Emery; Joshua W. Faulkner; et al. (Agricultural Systems, 2024)

Microplastics in oral healthcare products (OHPs) and their environmental health risks and mitigation measures - G.B Protyusha; Kavitha B; R.S Robin; Nithin A; T.R Ineyathendral; S. Shruthi Shivani; Anandavelu I; Shyam Sivasamy; V. Deepak Samuel; Purvaja R (Environmental Pollution, 2024)

Clinical, epidemiological, and molecular investigation of Kyasanur forest disease from Karnataka state, India during 2018-2019 - Ashok Munivenkatappa; Pragya D. Yadav; Rima R. Sahay; Kiran SK; Anita M. Shete; Deepak Y. Patil; Sreelekshmy Mohandas; Rajlaxmi Jain; Savita Patil; Diamond P. Sinha; Manjunatha M. Jayaswamy (Infectious Diseases, 2024)

Occurrence of Multidrug-Resistant (MDR) Extended-Spectrum Beta-lactamase (ESBL)-Producing Escherichia coli in Wastewater and Natural Water Sources from the Eastern Part of Uttar Pradesh, India - Kaushik Satyaprakash; Pavan Kumar Pesingi; Annada Das; M. R. Vineeth; Satya Veer Singh Malik; Sukhadeo B. Barbuddhe; Deepak Bhiwa Rawool (Water, Air, & Soil Pollution, 2024)

Insights into the characterization and therapeutic potential of Tasar silkworm pupal oil - Devika Srivastava; Deepak Kumar Tripathi; Vandana Singh; Krishna Mohan Poluri; Venkatesh Kumar R (Biocatalysis and Agricultural Biotechnology, 2024)

On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Utilizing Repeat UAV Imagery to Evaluate the Spatiotemporal Patterns and Environmental Drivers of Wrack in a Coastal Georgia Salt Marsh - Tyler Lynn; Merryl Alber; Jacob Shalack; Deepak R. Mishra (Estuaries and Coasts, 2024)

Israel−Palestine Conflict: Risk of Sleep Disorders and Post-Traumatic Stress Disorders - Seithikurippu R. Pandi‑Perumal; Kamalesh K. Gulia; Hruda Nanda Mallick; Deepak Shrivastava; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Konda Mani Saravanan; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Derebe Madoro; Meera Narasimhan; et al. (Sleep and Vigilance, 2023)

Assessment of benthic habitats of highly threatened oyster reefs of Pulicat Lake, India - Darwin Ramteke; K. Paramasivam; C. Viswanathan; K.R. Abhilash; J. Joyson Joe Jeevamani; V. Deepak Samuel; R. Sankar; R. Muruganandam; R. Purvaja; R. Ramesh (Regional Studies in Marine Science, 2023)

Comparative inhibitory screening of phytoconstituents from Capparis decidua against various ailments targets: a novel In-silico semblance ADME/Tox profiling studies - Rajendra S. Dave; Deepak Kumar Sharma; Kamlesh R. Shah (Advances in Traditional Medicine, 2023)

A Rural Delivery-Based Produce Prescription Intervention Improves Glycemic Control and Stress - Brandon Stroud; Molly M. Jacobs; Deepak Palakshappa; Lauren R. Sastre (Journal of Nutrition Education and Behavior, 2023)

Thunderstorm Nowcasting Using Ground-Based Microwave Radiometer Brightness Temperature Measurements - R. Pushpa Saroja; M. Rajasekhar; C. V. Naidu; S. Rambabu; G. Paparao; C. Deepak (Journal of the Indian Society of Remote Sensing, 2023)

Nanoencapsulation of biofunctional components as a burgeoning nanotechnology-based approach for functional food development: A review - Soubhagya Tripathy; Deepak Kumar Verma; Alok Kumar Gupta; Prem Prakash Srivastav; Ami R. Patel; Mónica L. Chávez González; Gemilang Lara Utama; Cristobal Noe Aguilar (Biocatalysis and Agricultural Biotechnology, 2023)

Differential impacts of post-harvest hydrothermal treatments on chemical composition and in vitro digestibility of two brown macroalgae (Fucales, Phaeophyceae), Ascophyllum nodosum and Fucus vesiculosus, for animal feed applications - Deepak Pandey; Geir Næss; António J. M. Fonseca; Margarida R. G. Maia; Ana R. J. Cabrita; Prabhat Khanal (Journal of Applied Phycology, 2023)
This study tested the hypothesis that post-harvest hot water blanching improves the chemical composition, mainly mineral and carbohydrate contents, and in vitro digestibility of two predominant brown macroalgae, Ascophyllum nodosum (AN) and Fucus vesiculosus (FV), as feed ingredients for monogastric and ruminant animals. Low-temperature water blanching (LTB; 40 °C for 5 min) had minor impacts on macroalgal chemical composition and in vitro digestibility. Conversely, high-temperature water blanching (HTB; 80 °C for 5 min) effectively reduced total ash and specific elements, including sodium, potassium, iodine, and arsenic, by ~ 25–73% compared to unblanched algal biomass (more prominently in FV). The HTB raised total sugar contents by ~ 25% in FV, markedly elevating uronic acids (~ 60%) and glucans (~ 33%). However, HTB reduced mannitol (> 50%) and enhanced total polyphenol extractability in both macroalgae. The HTB diminished ~ 8% of in vitro dry matter or organic matter digestibility and 26% of crude protein (CP) digestibility of both macroalgae for monogastric animals and of FV for ruminants (particularly of CP by ~ 42%). Those reduced digestibilities were associated with enriched fibre, uronic acids, total polyphenols, and declined mannitol in the HT-blanched macroalgal biomass. Our findings suggest that hot-water blanching can be an efficient technique to optimise the elemental composition of two fucoid algae, but the altered sugar and complex carbohydrate compositions may impair their digestibility. Future studies should identify appropriate post-harvest processing techniques for brown macroalgae that can optimise both nutritional composition and digestibility along with favourable impacts on feed utilisation and animal performance.

Investigating the mechanical strength, durability and micro-structural properties of slag-based concrete - M. Deepak; Y. Ramalinga Reddy; R. Nagendra (Innovative Infrastructure Solutions, 2023)

Atypical forcing embedded in typical forcing leading to the extreme summer 2020 precipitation in Nepal - Shankar Sharma; Kalpana Hamal; Binod Pokharel; Boniface Fosu; S.-Y. Simon Wang; Robert R. Gillies; Deepak Aryal; Archana Shrestha; Suresh Marahatta; Azfar Hussain; Nitesh Khadka (Climate Dynamics, 2023)

Harnessing unexplored medicinal values of the red listed South African weed Erigeron bonariensis: From ethnobotany to biomedicine - Vishal B. Mahanur; Rahul R. Rajge; Rashmi Saxena Pal; M.V.N.L. Chaitanya; Sukriti Vishwas; Saurabh Gupta; Gaurav Gupta; Deepak Kumar; Oluwafemi Omoniyi Oguntibeju; Zia ur Rehman; Faris F. Aba Alkhayl; Vinay Thakur; et al. (South African Journal of Botany, 2023)

High efficiency lipid production, biochar yield and chlorophyll a content of Chlorella sp. microalgae exposed on sea water and TiO2 nanoparticles - Rajasree Shanmuganathan; Quynh Hoang Le; Abeer S. Aloufi; Beata Gavurová; J.R. Deepak; Endalkachew Mosisa; Praveenkumar T. R (Environmental Research, 2023)

Enhancing secondary metabolites and alleviating environmental stress in crops with mycogenic nanoparticles: A comprehensive review - Deepak B. Shelke; Nazim F. Islam; Mahadev R. Chambhare; Hiralal B. Sonawane; Rupshikha Patowary; Ram Prasad; Hemen Sarma (Biocatalysis and Agricultural Biotechnology, 2023)

Imazethapyr-Resistant Jungle Rice (Echinochloa colona) in Soybean Growing Belt of Central India: A Case Study - Subhash Chander; Dibakar Ghosh; Vikas C. Tyagi; C. R. Chethan; Deepak Pawar; Yogita Gharde; Bhumesh Kumar; P. K. Singh (Agricultural Research, 2023)

Mutation spectrum and enzyme profiling of G6PD deficiency in neonates of north India: a prospective study - Upasana Bhattacharyya; Preeti Deswal; Sunil Kumar Polipalli; Diksha Sharma; Manpreet Kaur; Madhulika Kabra; Neerja Gupta; Ramesh Agarwal; A. K. Deorari; V. K. Paul; Shevendru Roy; R. K. Sanjeev; et al. (Journal of Genetics, 2023)

Enhanced pearl millet yield stability, water use efficiency and soil microbial activity using superabsorbent polymers and crop residue recycling across diverse ecologies - R.S. Bana; Minakshi Grover; Deepak Singh; Shanti D. Bamboriya; Samarth Godara; Manoj Kumar; Anil Kumar; Seema Sharma; P.S. Shekhawat; Dinesh Lomte; H.M. Bhuva; Sadhana R. Babar; et al. (European Journal of Agronomy, 2023)

Current State and Opportunities with Long-acting Injectables: Industry Perspectives from the Innovation and Quality Consortium “Long-Acting Injectables” Working Group - Andrea Bauer; Philippe Berben; Sudhir S. Chakravarthi; Sayantan Chattorraj; Ashish Garg; Betty Gourdon; Tycho Heimbach; Ye Huang; Christopher Morrison; Deepak Mundhra; Ramesh Palaparthy; Pratik Saha; et al. (Pharmaceutical Research, 2023)

Modelling crop yield and harvest index: the role of carbon assimilation and allocation parameters - Hector Camargo-Alvarez; Robert J. R. Elliott; Stefan Olin; Xuhui Wang; Chenzhi Wang; Deepak K. Ray; Thomas A. M. Pugh (Modeling Earth Systems and Environment, 2023)
Crop yield improvement during the last decades has relied on increasing the ratio of the economic organ to the total aboveground biomass, known as the harvest index (HI). In most crop models, HI is set as a parameter; this empirical approach does not consider that HI not only depends on plant genotype, but is also affected by the environment. An alternative is to simulate allocation mechanistically, as in the LPJ-GUESS crop model, which simulates HI based on daily growing conditions and the crop development stage. Simulated HI is critical for agricultural research due to its economic importance, but it also can validate the robust representation of production processes. However, there is a challenge to constrain parameter values globally for the allocation processes. Therefore, this paper aims to evaluate the sensitivity of yield and HI of wheat and maize simulated with LPJ-GUESS to eight production allocation-related parameters and identify the most suitable parameter values for global simulations. The nitrogen demand reduction after anthesis, the minimum leaf carbon to nitrogen ratio (C:N) and the range of leaf C:N strongly affected carbon assimilation and yield, while the retranslocation of labile stem carbon to grains and the retranslocation rate of nitrogen and carbon from vegetative organs to grains after anthesis mainly influenced HI. A global database of observed HI for both crops was compiled for reference to constrain simulations before calibrating parameters for yield against reference data. Two high- and low-yielding maize cultivars emerged from the calibration, whilst spring and winter cultivars were found appropriate for wheat. The calibrated version of LPJ-GUESS improved the simulation of yield and HI at the global scale for both crops, providing a basis for future studies exploring crop production under different climate and management scenarios.

Anthropogenic nitrogen pollution threats and challenges to the health of South Asian coral reefs - Stuart C. Painter; Yuri Artioli; Fathimath Hana Amir; Jessica Arnull; Raja S. Ganeshram; Nizam Ibrahim; V. Deepak Samuel; R.S. Robin; R. Raghuraman; R. Purvaja; R. Ramesh; Arjan Rajasuriya; et al. (Frontiers in Marine Science, 2023)
Nitrogen pollution is a widespread and growing problem in the coastal waters of South Asia yet the ecological impacts on the region’s coral ecosystems are currently poorly known and understood. South Asia hosts just under 7% of global coral reef coverage but has experienced significant and widespread coral loss in recent decades. The extent to which this coral ecosystem decline at the regional scale can be attributed to the multiple threats posed by nitrogen pollution has been largely overlooked in the literature. Here, we assess the evidence for nitrogen pollution impacts on corals in the central Indian Ocean waters of India, Sri Lanka and the Maldives. We find that there is currently limited evidence with which to clearly demonstrate widespread impacts on coral reefs from nitrogen pollution, including from its interactions with other stressors such as seawater warming. However, this does not prove there are no significant impacts, but rather it reflects the paucity of appropriate observations and related understanding of the range of potential impacts of nitrogen pollution at individual, species and ecosystem levels. This situation presents significant research, management and conservation challenges given the wide acceptance that such pollution is problematic. Following from this, we recommend more systematic collection and sharing of robust observations, modelling and experimentation to provide the baseline on which to base prescient pollution control action.

Dynamic emergent leaf area in tidal wetlands: Implications for satellite-derived regional and global blue carbon estimates - Peter A. Hawman; Deepak R. Mishra; Jessica L. O'Connell (Remote Sensing of Environment, 2023)

Mitigation of nitrous oxide emissions in grazing systems through nitrification inhibitors: a meta-analysis - Johnny R. Soares; Bruna R. Souza; André M. Mazzetto; Marcelo V. Galdos; Dave R. Chadwick; Eleanor E. Campbell; Deepak Jaiswal; Julianne C. Oliveira; Leonardo A. Monteiro; Murilo S. Vianna; Rubens A. C. Lamparelli; Gleyce K. D. A. Figueiredo; et al. (Nutrient Cycling in Agroecosystems, 2023)
Grasslands are the largest contributor of nitrous oxide (N 2 O) emissions in the agriculture sector due to livestock excreta and nitrogen fertilizers applied to the soil. Nitrification inhibitors (NIs) added to N input have reduced N 2 O emissions, but can show a range of efficiencies depending on climate, soil, and management conditions. A meta-analysis study was conducted to investigate the factors that influence the efficiency of NIs added to fertilizer and excreta in reducing N 2 O emissions, focused on grazing systems. Data from peer-reviewed studies comprising 2164 N 2 O emission factors (EFs) of N inputs with and without NIs addition were compared. The N 2 O EFs varied according to N source (0.0001–8.25%). Overall, NIs reduced the N 2 O EF from N addition by 56.6% (51.1–61.5%), with no difference between NI types (Dicyandiamide—DCD; 3,4-Dimethylpyrazole phosphate—DMPP; and Nitrapyrin) or N source (urine, dung, slurry, and fertilizer). The NIs were more efficient in situations of high N 2 O emissions compared with low; the reduction was 66.0% when EF > 1.5% of N applied compared with 51.9% when EF ≤ 0.5%. DCD was more efficient when applied at rates > 10 kg ha −1 . NIs were less efficient in urine with lower N content (≤ 7 g kg −1 ). NI efficiency was negatively correlated with soil bulk density, and positively correlated with soil moisture and temperature. Better understanding and management of NIs can optimize N 2 O mitigation in grazing systems, e.g., by mapping N 2 O risk and applying NI at variable rate, contributing to improved livestock sustainability.

Assessing the Effectiveness of Large-Scale Environmental Restoration: Challenges and Opportunities - Holly S. Greening; Kenneth L. Heck; Larry D. McKinney; Heida L. Diefenderfer; Walter R. Boynton; Barbara A. Kleiss; Deepak R. Mishra; Albert A. George; Bethany A. Carl Kraft; Cathy A. Kling; Laura A. Windecker (Estuaries and Coasts, 2023)

Effectiveness of Wheat Straw Biochar in Aqueous Zn Removal: Correlation with Biochar Characteristics and Optimization of Process Parameters - Divyesh R. Vaghela; Ashish Pawar; Deepak Sharma (BioEnergy Research, 2023)

Withaferin A, a steroidal lactone, selectively protects normal lymphocytes against ionizing radiation induced apoptosis and genotoxicity via activation of ERK/Nrf-2/HO-1 axis - Rahul Checker; H.N. Bhilwade; Shivani R. Nandha; Raghavendra S. Patwardhan; Deepak Sharma; Santosh K. Sandur (Toxicology and Applied Pharmacology, 2023)

Lessons, narratives, and research directions for a sustainable circular economy - Sina Leipold; Anna Petit‐Boix; Anran Luo; Hanna Helander; Machteld Simoens; Weslynne S. Ashton; Callie W. Babbitt; Alba Bala; Catharina R. Bening; Morten Birkved; Fenna Blomsma; Casper Boks; et al. (Journal of Industrial Ecology, 2023)
The current enthusiasm for the circular economy (CE) offers a unique opportunity to advance the impact of research on sustainability transitions. Diverse interpretations of CE by scholars, however, produce partly opposing assessments of its potential benefits, which can hinder progress. Here, we synthesize policy‐relevant lessons and research directions for a sustainable CE and identify three narratives—optimist, reformist, and skeptical—that underpin the ambiguity in CE assessments. Based on 54 key CE scholars’ insights, we identify three research needs: the articulation and discussion of ontologically distinct CE narratives; bridging of technical, managerial, socio‐economic, environmental, and political CE perspectives; and critical assessment of opportunities and limits of CE science–policy interactions. Our findings offer practical guidance for scholars to engage reflexively with the rapid expansion of CE knowledge, identify and pursue high‐impact research directions, and communicate more effectively with practitioners and policymakers.

Amplified drought trends in Nepal increase the potential for Himalayan wildfires - Binod Pokharel; Shankar Sharma; Jacob Stuivenvolt-Allen; Shih-Yu Simon Wang; Matthew LaPlante; Robert R. Gillies; Sujan Khanal; Michael Wehner; Alan Rhoades; Kalpana Hamal; Benjamin Hatchett; Wan-Yu Liu; et al. (Climatic Change, 2023)

Integrated management of Fusarium wilt disease of banana in Kerala, India - N. P. Lishma; K. Anita Cherian; Vimi Louis; R. Sureshkumar; P. Naveen Kumar; Deepak Chandran; M. Pran; Rohit Sharma (Vegetos, 2023)

Cases of SARS-CoV-2 reinfection with Omicron BA.2 post breakthrough infection with Delta and Kappa variants - Rima R. Sahay; Deepak Y. Patil; Gajanan N. Sapkal; Anita M. Shete; Pragya D. Yadav (Infectious Diseases, 2023)

Benthic foraminifera as an environmental proxy for pollutants along the coast of Chennai, India - K. Balachandar; C. Viswanathan; R.S. Robin; K.R. Abhilash; R. Sankar; V. Deepak Samuel; R. Purvaja; R. Ramesh (Chemosphere, 2023)

Toxicity potential evaluation of ethyl acetate extract of Cymodocea serrulata against the mosquito vectors vis-a-vis zebrafish embryos and Artemia salina cysts - V. Amutha; D. Aiswarya; P. Deepak; R. Selvaraj; C. Tamilselvan; P. Perumal; G. Balasubramani (South African Journal of Botany, 2023)

Co-occurrence patterns and environmental factors associated with rapid onset of Microcystis aeruginosa bloom in a tropical coastal lagoon - Lipika Tarafdar; Madhusmita Mohapatra; Pradipta R. Muduli; Abhishek Kumar; Deepak R. Mishra; Gurdeep Rastogi (Journal of Environmental Management, 2023)

Corrigendum to “Harmonization of acronyms for volatile organic compound metabolites using a standardized naming system” [Int. J. Hygiene Environ. Health 235 (2021) 113749] - Denise S. Tevis; Sharon R. Flores; Brandon M. Kenwood; Deepak Bhandari; Peyton Jacob; Jia Liu; Pawel K. Lorkiewicz; Daniel J. Conklin; Stephen S. Hecht; Maciej L. Goniewicz; Benjamin C. Blount; Víctor R. De Jesús (International Journal of Hygiene and Environmental Health, 2023)

Seasonal dynamics and polyphenism of butterfly communities in the coastal plains of central Western Ghats, India - Deepak Naik; R Shyama Prasad Rao; Krushnamegh Kunte; Mohammed S Mustak (Journal of Biosciences, 2022)

A comprehensive and quantitative assessment of Raunthi Gad flash flood, Rishi Ganga catchment, central Himalaya, Uttarakhand, India - Harish Chandra Nainwal; R. Shankar; Aditya Mishra; Sumit Mishra; Ankit Pandey; Sunil Singh Shah; Gambhir Singh Chauhan; Deepak Kumar (Natural Hazards, 2022)

Hot Melt Extrusion: an Emerging Green Technique for the Synthesis of High-Quality Pharmaceutical Cocrystals - Prabhakar S. Panzade; Giridhar R. Shendarkar; Deepak A. Kulkarni (Journal of Pharmaceutical Innovation, 2022)

Nearshore suspended sediment concentration and transport pattern along the southern Karnataka coast, India - Ateeth Shetty; K. S. Jayappa; P. R. Deepak; R. Ratheesh (Journal of Sedimentary Environments, 2022)

Proximate analysis, preliminary phytochemical screening and characterization of compounds by GC–MS from “Cycas revoluta” - Deepak Kumar Sharma; R. S. Dave; K. R. Shah (Vegetos, 2022)

Ecological monitoring and indicator taxa: butterfly communities in heterogeneous landscapes of the Western Ghats and Malabar coast, India - Deepak Naik; R. Shyama Prasad Rao; Krushnamegh Kunte; Mohammed S. Mustak (Journal of Insect Conservation, 2022)

COVID-19, the firestone in 21st century: a review on coronavirus disease and its clinical perspectives - Chenmala Karthika; R Swathy Krishna; Md. Habibur Rahman; Rokeya Akter; Deepak Kaushik (Environmental Science and Pollution Research, 2021)

Status of health and conservation classification of tropical coral reefs in Lakshadweep archipelago - M. Gopi; J. Joyson Joe Jeevamani; S. Goutham; Nina Tabitha Simon; V. Deepak Samuel; K. R. Abhilash; R. S. Robin; G. Hariharan; R. Muruganandam; P. Krishnan; R. Purvaja; R. Ramesh (Wetlands Ecology and Management, 2021)

Increasing signs of degradation of shallow water coral reefs due to repeated bleaching and spatial competition among benthic substrates - Bitopan Malakar; S. Venu; V. Deepak Samuel; K. R. Abhilash (Wetlands Ecology and Management, 2021)

Lower cardiac output is associated with neurodegeneration among older adults with normal cognition but not mild cognitive impairment - Elizabeth E. Moore; Dandan Liu; Corey W. Bown; Hailey A. Kresge; Deepak K. Gupta; Kimberly R. Pechman; Lisa A. Mendes; L. Taylor Davis; Katherine A. Gifford; Adam W. Anderson; Thomas J. Wang; Bennett A. Landman; et al. (Brain Imaging and Behavior, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Corrigendum: Effect of COVID-19 Anthropause on Water Clarity in the Belize Coastal Lagoon - Ileana A. Callejas; Christine M. Lee; Deepak R. Mishra; Stacey L. Felgate; Claire Evans; Abel Carrias; Andria Rosado; Robert Griffin; Emil A. Cherrington; Mariam Ayad; Megha Rudresh; Benjamin P. Page; et al. (Frontiers in Marine Science, 2021)

Middle East Respiratory Syndrome (MERS) Virus—Pathophysiological Axis and the Current Treatment Strategies - Abdullah M Alnuqaydan; Abdulmajeed G Almutary; Arulmalar Sukamaran; Brian Tay Wei Yang; Xiao Ting Lee; Wei Xuan Lim; Yee Min Ng; Rania Ibrahim; Thiviya Darmarajan; Satheeshkumar Nanjappan; Jestin Chellian; Mayuren Candasamy; et al. (AAPS PharmSciTech, 2021)

Effect of COVID-19 Anthropause on Water Clarity in the Belize Coastal Lagoon - Ileana A. Callejas; Christine M. Lee; Deepak R. Mishra; Stacey L. Felgate; Claire Evans; Abel Carrias; Andria Rosado; Robert Griffin; Emil A. Cherrington; Mariam Ayad; Megha Rudresh; Benjamin P. Page; et al. (Frontiers in Marine Science, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic halted human activities globally in multiple sectors including tourism. As a result, nations with heavy tourism, such as Belize, experienced improvements in water quality. Remote sensing technologies can detect impacts of “anthropauses” on coastal water quality. In this study, moderate resolution imaging spectroradiometer (MODIS) satellite data were employed along the Belizean coast to investigate impacts of the COVID-19 shutdown on water quality. The attenuation coefficient at 490 nm, K d (490), was used as an indicator of water quality, with a lower K d (490) indicating increased water clarity. Four Coastal Management Zones were characterized by marine traffic as high traffic areas (HTAs) and two as low traffic areas (LTAs). Monthly composites for two periods, 2002–2019 (baseline) and 2020 were examined for K d (490). For months prior to the COVID-19 shutdown in Belize, there was generally no significant difference in K d (490) ( p > 0.05) between 2020 and baseline period in HTAs and LTAs. Through the shutdown, K d was lower in 2020 at HTAs, but not for LTAs. At the LTAs, the K d (490)s observed in 2020 were similar to previous years through October. In November, an unusually active hurricane season in 2020 was associated with decreased water clarity along the entire coast of Belize. This study provides proof of concept that satellite-based monitoring of water quality can complement in situ data and provide evidence of significant water quality improvements due to the COVID-19 shutdown, likely due to reduced marine traffic. However, these improvements were no longer observed following an active hurricane season.

N-Benzylation of 6-aminoflavone by reductive amination and efficient access to some novel anticancer agents via topoisomerase II inhibition - Nitin M. Thorat; Aniket P. Sarkate; Deepak K. Lokwani; Shailee V. Tiwari; Rajaram Azad; Shankar R. Thopate (Molecular Diversity, 2021)

An integrated approach to assess coastal vulnerability versus fisheries livelihood sustainability: Strategies for climate change adaptation in Sindhudurg, west coast of India - J. Joyson Joe Jeevamani; P. Priya; J. Amali Infantina; K. R. Abhilash; Durga Prasad Behera; V. Deepak Samuel; R. Soundararajan; R. Purvaja; R. Ramesh (Environment, Development and Sustainability, 2021)

Polyphasic Characterization of Plant Growth Promoting Cellulose Degrading Bacteria Isolated from Organic Manures - Devendra Jain; Ravina; Ali Asger Bhojiya; Surya Chauhan; Deepak Rajpurohit; Santosh R. Mohanty (Current Microbiology, 2021)

In an exploratory randomized, double-blind, placebo-controlled, cross-over study, psychoactive doses of intravenous delta-9-tetrahydrocannabinol fail to produce antinociceptive effects in healthy human volunteers - Emmanuelle A. D. Schindler; Ashley M. Schnakenberg Martin; R. Andrew Sewell; Mohini Ranganathan; Anna DeForest; Brian P. Pittman; Albert Perrino; Deepak C. D’Souza (Psychopharmacology, 2020)

Green transamidation catalysed by graphene oxide under concentrated solar irradiation - Khushbu P. Patel; Sujit S. Kamble; Deepak R. Boraste; Ganapati S. Shankarling (Environmental Chemistry Letters, 2020)

Chemical composition, antioxidant and antiproliferative activities of essential oil from rhizome and leaves of Curcuma mutabilis Škorničk., M. Sabu & Prasanthk., endemic to Western Ghats of India - T. Soumya; P. R. Jayasree; M. Deepak; P. R. Manish Kumar (Natural Product Research, 2020)

Efficacy of Indolicidin, Cecropin A (1-7)-Melittin (CAMA) and Their Combination Against Biofilm-Forming Multidrug-Resistant Enteroaggregative Escherichia coli - Jess Vergis; S. V. S. Malik; Richa Pathak; Manesh Kumar; R. Sunitha; S. B. Barbuddhe; Deepak B. Rawool (Probiotics and Antimicrobial Proteins, 2020)

Assessment of yield gaps on global grazed‐only permanent pasture using climate binning - Leonardo A. Monteiro; Andrew M. Allee; Eleanor E. Campbell; Lee R. Lynd; Johnny R. Soares; Deepak Jaiswal; Julianne de Castro Oliveira; Murilo dos Santos Vianna; Ashley E. Morishige; Gleyce K. D. A. Figueiredo; Rubens A. C. Lamparelli; Nathaniel D. Mueller; et al. (Global Change Biology, 2020)
To meet rising demands for agricultural products, existing agricultural lands must either produce more or expand in area. Yield gaps (YGs)—the difference between current and potential yield of agricultural systems—indicate the ability to increase output while holding land area constant. Here, we assess YGs in global grazed‐only permanent pasture lands using a climate binning approach. We create a snapshot of circa 2000 empirical yields for meat and milk production from cattle, sheep, and goats by sorting pastures into climate bins defined by total annual precipitation and growing degree‐days. We then estimate YGs from intra‐bin yield comparisons. We evaluate YG patterns across three FAO definitions of grazed livestock agroecosystems (arid, humid, and temperate), and groups of animal production systems that vary in animal types and animal products. For all subcategories of grazed‐only permanent pasture assessed, we find potential to increase productivity several‐fold over current levels. However, because productivity of grazed pasture systems is generally low, even large relative increases in yield translated to small absolute gains in global protein production. In our dataset, milk‐focused production systems were found to be seven times as productive as meat‐focused production systems regardless of animal type, while cattle were four times as productive as sheep and goats regardless of animal output type. Sustainable intensification of pasture is most promising for local development, where large relative increases in production can substantially increase incomes or “spare” large amounts of land for other uses. Our results motivate the need for further studies to target agroecological and economic limitations on productivity to improve YG estimates and identify sustainable pathways toward intensification.

Systematic precipitation redistribution following a strong hurricane landfall - Paul W. Miller; Thomas L. Mote; Abhishek Kumar; Deepak R. Mishra (Theoretical and Applied Climatology, 2020)

Impact of anthropogenic interferences on species composition, regeneration and stand quality in moist temperate forests of Central Himalaya - Shalini Dhyani; R. K. Maikhuri; Deepak Dhyani (Tropical Ecology, 2019)

Impact of Land Use Land Cover (LULC) Change on Surface Runoff in an Increasingly Urbanized Tropical Watershed - Ike Sari Astuti; Kamalakanta Sahoo; Adam Milewski; Deepak R. Mishra (Water Resources Management, 2019)

Genome-wide promoter DNA methylation profiling of hepatocellular carcinomas arising either spontaneously or due to chronic exposure to Ginkgo biloba extract (GBE) in B6C3F1/N mice - Ramesh C. Kovi; Sachin Bhusari; Deepak Mav; Ruchir R. Shah; Thai Vu Ton; Mark J. Hoenerhoff; Robert C. Sills; Arun R. Pandiri (Archives of Toxicology, 2019)

Impact of multiyear La Niña events on the South and East Asian summer monsoon rainfall in observations and CMIP5 models - S. N. Raj Deepak; Jasti S. Chowdary; A. Ramu Dandi; G. Srinivas; Anant Parekh; C. Gnanaseelan; R. K. Yadav (Climate Dynamics, 2019)

Reduction of the carbon footprint of college freshman diets after a food-based environmental science course - Jennifer A. Jay; Raffaella D’Auria; J. Cully Nordby; David Andy Rice; David A. Cleveland; Anthony Friscia; Sophie Kissinger; Marc Levis; Hannah Malan; Deepak Rajagopal; Joel R. Reynolds; Wendelin Slusser; et al. (Climatic Change, 2019)

Impact of long-term seaweed farming on water quality: a case study from Palk Bay, India - K. R. Abhilash; R. Sankar; R. Purvaja; Samuel V. Deepak; C. R. Sreeraj; P. Krishnan; V. Sekar; Amit K. Biswas; G. Kumarapandiyan; R. Ramesh (Journal of Coastal Conservation, 2019)

Optimization of in vitro regeneration of Haloxylon salicornicum: a keystone species of extreme arid regions - Deepak Krishna Vyas; Harchand R. Dagla (Physiology and Molecular Biology of Plants, 2018)

Mapping freshwater marsh species in the wetlands of Lake Okeechobee using very high-resolution aerial photography and lidar data - Caiyun Zhang; Sara Denka; Deepak R. Mishra (International Journal of Remote Sensing, 2018)

Cytological and immunocytological detection and differentiation of Marek’s disease and lymphoid leucosis in poultry - M. Asok Kumar; M. Palanivelu; R. Barathidasan; Deepak Kumar; S. D. Singh; Shyma K. Lateef; Rajendra Singh; K. Dhama (VirusDisease, 2018)

Stable, fertile somatic hybrids between Sinapis alba and Brassica juncea show resistance to Alternaria brassicae and heat stress - Preetesh Kumari; Deepak Singh Bisht; Shripad R. Bhat (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Applicability of HEC-RAS & GFMS tool for 1D water surface elevation/flood modeling of the river: a Case Study of River Yamuna at Allahabad (Sangam), India - Neeraj Kumar; Deepak Lal; Arpan Sherring; R. K. Issac (Modeling Earth Systems and Environment, 2017)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Comparative diagnostic evaluation of OMP31 gene based TaqMan® real-time PCR assay with visual LAMP assay and indirect ELISA for caprine brucellosis - Suman Saini; V. K. Gupta; K. Gururaj; D. D. Singh; R. V. S. Pawaiya; N. K. Gangwar; A. K. Mishra; Deepak Dwivedi; Dimple Andani; Ashok Kumar; T. K. Goswami (Tropical Animal Health and Production, 2017)

Differential Impact of Anniversary-Severe Cyclones on the Water Quality of a Tropical Coastal Lagoon - Abhishek Kumar; Deepak R. Mishra; Sk. Md. Equeenuddin; Hyun Jung Cho; Gurdeep Rastogi (Estuaries and Coasts, 2017)

Impact of Heavy Metal Containing Wastewater on Agricultural Soil and Produce: Relevance of Biological Treatment - Deepak Gola; Anushree Malik; Ziauddin Ahammad Shaikh; T. R. Sreekrishnan (Environmental Processes, 2016)

On selection and scaling of ground motions for analysis of seismically isolated structures - Deepak R. Pant; Manika Maharjan (Earthquake Engineering and Engineering Vibration, 2016)

Preferential binding to dopamine D3 over D2 receptors by cariprazine in patients with schizophrenia using PET with the D3/D2 receptor ligand [11C]-(+)-PHNO - Ragy R. Girgis; Mark Slifstein; Deepak D’Souza; Yih Lee; Antonia Periclou; Parviz Ghahramani; István Laszlovszky; Suresh Durgam; Nika Adham; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; et al. (Psychopharmacology, 2016)
Rationale Second-generation antipsychotics occupy dopamine D 2 receptors and act as antagonists or partial agonists at these receptors. While these drugs alleviate positive symptoms in patients with schizophrenia, they are less effective for treating cognitive deficits and negative symptoms. Dopamine D 3 receptors are highly expressed in areas of the brain thought to play a role in the regulation of motivation and reward-related behavior. Consequently, the dopamine D 3 receptor has become a target for treating negative symptoms in combination with D 2 antagonism to treat positive symptoms in patients with schizophrenia. Objective The purpose of this study was to determine the cariprazine receptor occupancies in brain for D 2 and D 3 receptors in patients with schizophrenia. Methods Using [ 11 C]-(+)-PHNO as a radioligand, positron emission tomography (PET) scans were performed in eight patients at baseline and postdose on days 1, 4, and 15. Plasma and cerebrospinal fluid (CSF) samples were analyzed for cariprazine concentrations. Results A monotonic dose-occupancy relationship was observed for both receptor types. After 2 weeks of treatment, near complete (∼100 %) occupancies were observed for both receptors at a dose of 12 mg/day. At the lowest cariprazine dose (1 mg/day), mean D 3 and D 2 receptor occupancies were 76 and 45 %, respectively, suggesting selectivity for D 3 over D 2 receptors at low doses. An exposure-response analysis found a ∼3-fold difference in EC 50 (D 3 = 3.84 nM and D 2 = 13.03 nM) in plasma after 2 weeks of dosing. Conclusion This PET imaging study in patients with schizophrenia demonstrated that cariprazine is a D 3 -preferring dual D 3 /D 2 receptor partial agonist.

Analyzing the status of submerged aquatic vegetation using novel optical parameters - Luiz H. S. Rotta; Deepak R. Mishra; Enner H. Alcântara; Nilton N. Imai (International Journal of Remote Sensing, 2016)

Homology modeling and molecular docking studies of ArnA protein from Erwinia amylovora: role in polymyxin antibiotic resistance - Kailas D. Sonawane; Rishikesh S. Parulekar; Radhika S. Malkar; Pranhita R. Nimbalkar; Sagar H. Barage; Deepak B. Jadhav (Journal of Plant Biochemistry and Biotechnology, 2015)

Tidal Influence on the Diel Vertical Migration Pattern of Zooplankton in a Tropical Monsoonal Estuary - G. Vineetha; R. Jyothibabu; N. V. Madhu; K. K. Kusum; P. M. Sooria; A. Shivaprasad; P. D. Reny; M. P. Deepak (Wetlands, 2015)

Oleanane triterpenoids in the prevention and therapy of breast cancer: current evidence and future perspectives - Nisha R. Parikh; Animesh Mandal; Deepak Bhatia; Kodappully Sivaraman Siveen; Gautam Sethi; Anupam Bishayee (Phytochemistry Reviews, 2014)

Effects of Δ9-tetrahydrocannabinol in individuals with a familial vulnerability to alcoholism - Mohini Ranganathan; R. Andrew Sewell; Michelle Carbuto; Jacqueline Elander; Ashley Schnakenberg; Rajiv Radhakrishnan; Brian Pittman; Deepak Cyril D’Souza (Psychopharmacology, 2014)

Polymorphism of cytokine and innate immunity genes associated with bovine brucellosis in cattle - Om Prakash; Amit Kumar; Arvind Sonwane; Rajesh Rathore; Ran Vir Singh; Anuj Chauhan; Pushpendra Kumar; R. Renjith; Ramji Yadav; Ashish Bhaladhare; Mohd Baqir; Deepak Sharma (Molecular Biology Reports, 2014)

Correlation of human S100A12 (EN-RAGE) and high-sensitivity C-reactive protein as gingival crevicular fluid and serum markers of inflammation in chronic periodontitis and type 2 diabetes - A. R. Pradeep; Santosh S. Martande; Sonender Pal Singh; Deepak Kumar Suke; Arjun P. Raju; Savitha B. Naik (Inflammation Research, 2014)

Trends in temperature over Godavari River basin in Southern Peninsular India - Deepak Jhajharia; Yagob Dinpashoh; Ercan Kahya; Rahul R. Choudhary; Vijay P. Singh (International Journal of Climatology, 2014)
There is little dispute that global surface air temperature has increased and the anthropogenic‐induced global warming is likely to play an important role in the management of water resources of a river basin. Therefore, this study was undertaken for Godavari River basin, a large southern peninsular river basin in India. After removing the effect of significant lag‐1 serial correlation by pre‐whitening procedure, the Mann–Kendall ( MK ) test was employed to investigate trends in maximum temperature ( T max ), minimum temperature ( T min ) and mean temperature ( T mean ) at 35 stations in the basin. At seasonal (monthly) time scales, a majority of the stations exhibited no trends in T mean , T max and T min in any of the four seasons (12 months) with the exception of post‐monsoon (December) for T max and monsoon (July and September) for T min . About 60% (45%) of the stations exhibited increasing trends in T max ( T min ) in different durations: the month of December and post‐monsoon season (the months of July and September and monsoon season) indicating the presence of an element of seasonal cycle in temperature over the Godavari basin. Results of tests of spatial and temporal homogeneity of trends by the Van Belle and Hughes method showed that trends in temperature over the Godavari basin were not homogeneous for different months or at different stations. In spite of the warmer climate in the basin, the evaporation (Epan) has been found to decrease significantly over the Godavari basin. Strong decreases in wind speed and increases in relative humidity may have actually caused the Epan decreases over the southern peninsular region of India.

A new ensemble-based data assimilation algorithm to improve track prediction of tropical cyclones - Deepak Subramani; R. Chandrasekar; K. Srinivasa Ramanujam; C. Balaji (Natural Hazards, 2014)

Residual-state creep behavior of typical clayey soils - Deepak R. Bhat; N. P. Bhandary; R. Yatabe (Natural Hazards, 2013)

The first multituberculate mammal from India - Varun Parmar; Guntupalli V. R. Prasad; Deepak Kumar (The Science of Nature, 2013)

Assessing anthropogenic pressure and its impact on Hippophae salicifolia pockets in Central Himalaya, Uttarakhand - Deepak Dhyani; Shalini Dhyani; R. K. Maikhuri (Journal of Mountain Science, 2013)

Pharmacokinetics and Metabolism of 2-Aminothiazoles with Antiprion Activity in Mice - B. Michael Silber; Satish Rao; Kimberly L. Fife; Alejandra Gallardo-Godoy; Adam R. Renslo; Deepak K. Dalvie; Kurt Giles; Yevgeniy Freyman; Manuel Elepano; Joel R. Gever; Zhe Li; Matthew P. Jacobson; et al. (Pharmaceutical Research, 2013)

Influence of climate on incidences of malaria in the Thar Desert, northwest India - Deepak Jhajharia; Surajit Chattopadhyay; Rahul R. Choudhary; Vas Dev; Vijay P. Singh; Shankar Lal (International Journal of Climatology, 2013)
Climatic variability and rise in temperature are considered as the key determinants to the transmission of malaria. In the present study, the trends in the cases of malaria caused by Plasmodium falciparum and Plasmodium vivax were investigated by using the nonparametric Mann‐Kendall test after removing the effect of significant lag‐1 serial correlation from the time series of cases of malaria incidence by pre‐whitening in annual, seasonal, and monthly time scales at Bikaner, located in the Thar Desert of Rajasthan, in northwest India. Multi‐collinearity within the datasets under consideration was investigated by means of correlation matrix, the Bartlett sphericity test, and the Kaiser‐Meyer‐Olkin measure of sampling adequacy, subsequent to which it was removed by using principal component analysis. Finally, artificial neural network models were employed to predict cases of malaria incidence caused by P. falciparum and P. vivax at various scales. During the last 34 years from 1975 to 2008, P. falciparum malaria incidence cases have been found to increase significantly corresponding to monthly (April and September) and seasonal (monsoon) time scales over Bikaner. On the other hand, no significant trends were observed in P. vivax malaria cases at Bikaner. Concomitant increases in P. falciparum cases of malaria incidence and observed temperature increases at Bikaner hint that P. falciparum malaria may have grown significantly under the warming climate of the Thar Desert. Copyright © 2012 Royal Meteorological Society

Synthesis and antimicrobial activity of 5-((3-aryl-1-phenyl-1H-pyrazol-4-yl)methylene)thiazolidine-2,4-diones - Om Prakash; Deepak K. Aneja; Poonam Lohan; Khalid Hussain; Sanjiv Arora; Chetan Sharma; Kamal R. Aneja (Medicinal Chemistry Research, 2012)

Molecular analysis of gut microbiota in obesity among Indian individuals - Deepak P Patil; Dhiraj P Dhotre; Sachin G Chavan; Armiya Sultan; Dhawal S Jain; Vikram B Lanjekar; Jayshree Gangawani; Poonam S Shah; Jayshree S Todkar; Shashank Shah; Dilip R Ranade; Milind S Patole; et al. (Journal of Biosciences, 2012)

The safety of studies with intravenous Δ9-tetrahydrocannabinol in humans, with case histories - Michelle Carbuto; R. Andrew Sewell; Ashley Williams; Kim Forselius-Bielen; Gabriel Braley; Jacqueline Elander; Brian Pittman; Ashley Schnakenberg; Savita Bhakta; Edward Perry; Mohini Ranganathan; Deepak Cyril D’Souza (Psychopharmacology, 2012)

Synthesis and antimicrobial activities of some new 5-((3-(aryl)-1-phenyl-1H-pyrazol-4-yl)methylene)-3-phenylthiazolidine-2,4-diones - Om Prakash; Deepak Kumar Aneja; Sanjiv Arora; Chetan Sharma; K. R. Aneja (Medicinal Chemistry Research, 2012)

The first draft of the pigeonpea genome sequence - Nagendra K. Singh; Deepak K. Gupta; Pawan K. Jayaswal; Ajay K. Mahato; Sutapa Dutta; Sangeeta Singh; Shefali Bhutani; Vivek Dogra; Bikram P. Singh; Giriraj Kumawat; Jitendra K. Pal; Awadhesh Pandit; et al. (Journal of Plant Biochemistry and Biotechnology, 2012)

A Fluorescence and Fluorescence Probe Study of Benzonaphthyridines - Deepak Prakash Shelar; Sandeep R. Patil; Ramhari V. Rote; Madhukar N. Jachak (Journal of Fluorescence, 2012)

Screening new Arachis amphidiploids, and autotetraploids for resistance to late leaf spot by detached leaf technique - Nalini Mallikarjuna; Deepak R. Jadhav; Kanaka Reddy; Fatema Husain; Kumkum Das (European Journal of Plant Pathology, 2012)

A Fluorescence Study of New Angular Polycyclic Blue Light-Emitting pyrazolo[3,4-h][1,6]naphthyridine and their Interaction with Bovine Serum Albumin (BSA) - Sandeep R. Patil; Deepak P. Shelar; Ramhari V. Rote; Madhukar N. Jachak (Journal of Fluorescence, 2011)

Cajanus platycarpus (Benth.) Maesen as the donor of new pigeonpea cytoplasmic male sterile (CMS) system - Nalini Mallikarjuna; Deepak R. Jadhav; Sandhya Srikanth; Kulbhushan B. Saxena (Euphytica, 2011)

Synthesis and Fluorescence Investigation of Differently Substituted Benzo[b][1,8]Naphthyridines: Interaction with Different Solvents and Bovine Serum Albumin (BSA) - Deepak P. Shelar; Sandeep R. Patil; Ramhari V. Rote; Raghunath B. Toche; Madhukar N. Jachak (Journal of Fluorescence, 2011)

Genetic diversity analysis of maintainer and restorer accessions in upland cotton (Gossypium hirsutum L.) - Deepak R. Sapkal; Satish R. Sutar; Prajwal B. Thakre; Bhaskar R. Patil; Andrew H. Paterson; Vijay N. Waghmare (Journal of Plant Biochemistry and Biotechnology, 2011)

Effect of Specific Solute-Solvent Interaction and Electron Donor-Acceptor Substituents of Novel Pyrazolo Naphthyridines on Fluorescence - Sandeep R. Patil; Deepak P. Shelar; Ramhari V. Rote; Raghunath B. Toche; Madhukar N. Jachak (Journal of Fluorescence, 2011)

Effect of Donor-Acceptor Chromophores on Photophysical Properties of Newly Synthesized Pyrazolo-Pyrrolo-Pyrimidines (PPP) - Ramhari V. Rote; Deepak P. Shelar; Sandeep R. Patil; Santosh S. Shinde; Raghunath B. Toche; Madhukar N. Jachak (Journal of Fluorescence, 2011)

A metabolic and functional overview of brain aging linked to neurological disorders - Najma Z. Baquer; Asia Taha; Pardeep Kumar; P. McLean; S. M. Cowsik; R. K. Kale; R. Singh; Deepak Sharma (Biogerontology, 2009)

Effect of dehydroepiandrosterone (DHEA) on monoamine oxidase activity, lipid peroxidation and lipofuscin accumulation in aging rat brain regions - Pardeep Kumar; Asia Taha; Deepak Sharma; R. K. Kale; Najma Z. Baquer (Biogerontology, 2008)

Effect of dehydroepiandrosterone (DHEA) on monoamine oxidase activity, lipid peroxidation and lipofuscin accumulation in aging rat brain regions - Pardeep Kumar; Asia Taha; Deepak Sharma; R. K. Kale; Najma Z. Baquer (Biogerontology, 2008)

Effect of herbal polyphenols on atherogenic transcriptome - Deepak Kaul; Akshay R. Shukla; Kavleen Sikand; Veena Dhawan (Molecular and Cellular Biochemistry, 2005)

Semen characteristics: Advancement in andrological assessment - R. S. Sharma; K. K. Gaur; P. C. Pal; Monika Manocha; Deepak Tomar; Arif Azam Khan; Vinita Tripathi; Vineeta Chattree; A. Kriplani (Indian Journal of Clinical Biochemistry, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Studies on some trace and minor elements in blood - T. R. Mahalingam; S. Vijayalashmi; R. Krishna Prabhu; A. Thiruvengadasami; K. S. R. Murthy; Deepak Sen; C. K. Mathews; K. Radha Shanmugasundaram (Biological Trace Element Research, 1997)

Pathobiochemical response of tracheobronchial lymph nodes following intratracheal instillation of Polyvinylchloride dust in rats - Deepak K. Agarwal; R. K. S. Dogra; Ravi Shanker (Archives of Toxicology, 1991)

Comparison of the enzymatic composition of cell-free extracts of non-aflatoxigenicAspergillus parasiticus with respect to late stages of aflatoxin biosynthesis - Deepak Bhatnagar; Thomas E. Cleveland; Alan R. Lax (Archives of Environmental Contamination and Toxicology, 1989)